Biometric alterations in thoracic limbs of vaquejada horses - Torres, Paula Barbosa; Santiago, Juliano Martins; Lucena, Jorge Eduardo Cavalcante; Gonzaga, Iaçanã Valente Ferreira; Melo, Daniel Ânderson de Souza; Lima, Gustavo Simões; Silva, Andreza Correia da; Macedo, Alisson Vinícius Mota (Medicina Veterinária, 2022)
This study aimed to determine the frequency of biometric alterations in thoracic limbs of vaquejada horses. A sample of 1,270 horses of either sex and different age groups competing in vaquejada as either puxador (leading) or esteira (trailing) roles were used. Measurements were made of body length, thoracic circumference, and circumferences of the forearm, knee, cannon, fetlock, and pastern of the right- and left-side thoracic limbs. Asymmetry in the five regions of thoracic limbs was also determined by calculating the difference between the right- and left-side circumferences of each region. Physical examination was conducted in 598 horses by palpating the knee, cannon, fetlock, and pastern to identify possible orthopedic alterations. The results of the differences between the circumferences of thoracic limbs of either side were submitted to Kruskal-Wallis test and the prevalence of orthopedic alterations was compared by frequency distribution test. Asymmetry was observed between the right- and left-side thoracic limbs in 99.3% of horses, especially in the forearm. Of the 598 horses examined via palpation, 481 individuals (80.4%) exhibited orthopedic alterations in at least one of the four regions examined, with the highest prevalence of alterations in the cannon and fetlock. In addition, the proportions of individuals with orthopedic alterations increased linearly with age, while higher values in the conformation and dactyl-thoracic indices also resulted in higher prevalence of alterations. It was concluded that the frequency of biometric alterations in thoracic limbs of vaquejada horses is high.